No time to retreat : why we must solidify multicultural education - Obiakor, Festus E. (Emerald Publishing Limited, 2025)
While there is much goodness in today's world, it often feels like the world is ablaze. Across all regions, we face conflicts, wars, inhumane actions, racism, xenophobia, crimes against humanity, poverty, social injustice, and other forms of hatred. As global citizens, we seem to have forgotten the value of our multicultural world and the importance of embracing our differences. No Time to Retreat: Why We Must Solidify Multicultural Education is a book that acknowledges these challenges and advocates for leveraging our diverse thoughts, talents, strengths, and skills to create a more liveable world. Our global problems are evident in our nations, communities, organizations, institutions, schools, and among individuals. In the United States, for example, many of our multicultural gains in diversity, equity, and inclusion (DEI) are under attack; and our hard-fought freedoms are eroding. This book reminds us that we are in this together and urges us to shift paradigms, refocus our energies, and realign our vision and strategies to achieve our goals. On the whole, this book emphasizes that now is "no time to retreat" and that we must "solidify multicultural education."